2012
DOI: 10.1073/pnas.1215421109
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeted gene disruption in Xenopus embryos using engineered transcription activator-like effector nucleases (TALENs)

Abstract: Transcription activator-like effector nucleases (TALENs) are an approach for directed gene disruption and have been proved to be effective in various animal models. Here, we report that TALENs can induce somatic mutations in Xenopus embryos with reliably high efficiency and that such mutations are heritable through germ-line transmission. We modified the Golden Gate method for TALEN assembly to make the product suitable for RNA transcription and microinjection into Xenopus embryos. Eight pairs of TALENs were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
200
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 226 publications
(207 citation statements)
references
References 25 publications
6
200
0
1
Order By: Relevance
“…Unlike ZFNs, TALENs have fewer off-target effects and lower toxicity. Given the success of the TALEN technology in reported species [4][5][6], we attempted to explore the feasibility of producing KO rabbits using this technology. In the current study, we chose recombination activation genes (RAGs), including RAG1 and RAG2, as the first genes of interest.…”
mentioning
confidence: 99%
“…Unlike ZFNs, TALENs have fewer off-target effects and lower toxicity. Given the success of the TALEN technology in reported species [4][5][6], we attempted to explore the feasibility of producing KO rabbits using this technology. In the current study, we chose recombination activation genes (RAGs), including RAG1 and RAG2, as the first genes of interest.…”
mentioning
confidence: 99%
“…This modified TALEN platform was used to efficiently induce mutations in Xenopus and zebrafish. Although previous studies have shown that TALEN has high specificity (Bogdanove and Voytas 2011;Huang et al 2011;Hwang et al 2013;Lei et al 2012;Liu et al 2013Liu et al , 2014Sander et al 2011), offtarget problems remained underestimated. On the one hand, while HD, NI, and NG RVDs of TALENs could specifically correspond with C, A, and T, only NN can identify both G and A, indicating that the more G in the target sequence, the more NN is required in the corresponding synthetic TALEN artificial nucleases, but this increases the opportunity for nonspecific knockouts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-specific cleavage of the genome can cause cytotoxic or embryotoxic effects. Compared with ZFN, the TALEN technique displays a broader recognition property for DNA sequences and, in fact, it is hardly ever affected by DNA sequence even though it has high sequence-specific recognition (Lei et al 2012;Liu et al 2013). Hence, we aimed to explore the application of TALENs in medaka and other fish to promote the study of genetic engineering and gene function in fish.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19] TALEN-mediated gene targeting has also been successfully demonstrated in several systems including plants, 20,21 zebrafish, 22 yellow catfish, 23 Caenorhabditis elegans, 24 rats, 25 mice 26 and human cells. 3 To date, conventional plasmids, 3,20,[27][28][29][30][31][32] integrase-defective lentiviral vectors, 18,33 adenoviral vectors, 34,35 adeno-associated viral vectors, 36 direct microinjection into embryos, 12,[37][38][39] and recombinant proteins 40,41 have been used to deliver engineered nucleases. Among these approaches, plasmid-mediated delivery has been predominant because it is easy to generate the necessary components and vector integration into the host genome is relatively rare.…”
Section: Introductionmentioning
confidence: 99%